Concomitant Deep Venous Thrombosis, Femoral Artery Thrombosis, and Pulmonary Embolism after Air Travel - Salim Abunnaja; Marshall Clyde; Andrea Cuviello; Robert A. Brenes; Giuseppe Tripodi (Case Reports in Vascular Medicine)
The association between air travel and deep venous thrombosis and/or pulmonary embolism “economy-class syndrome” is well described. However, this syndrome does not describe any association between long duration travel and arterial thrombosis or coexistence of venous and arterial thrombosis. We present a case of concomitant deep venous thrombosis, acute femoral artery thrombosis, and bilateral pulmonary embolisms in a patient following commercial air travel. Echocardiogram did not reveal an intracardiac shunt that may have contributed to the acute arterial occlusion from a paradoxical embolus. To our knowledge, this is the first report in the literature that associates air traveling with both arterial and venous thrombosis.